ПРАКТИЧНІ МЕХАНІЗМИ ПРОДУКУВАННЯ ЕТИЧНО ДІЄВОГО РИТОРИЧНОГО ДИСКУРСУ НА УРОКАХ МОВИ В ОСНОВНІЙ ШКОЛІ - Воробйова, Алла (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті з’ясовується зміст і значення етичного спілкування у процесі становлення ідеальної риторичної особистості. У дослідженні визначено сутнісні елементи риторичного дискурсу (предмет, продукт, засоби реалізації), подано змістовні характеристики етичності публічної промови, проаналізовано аспекти продукування етично дієвого риторичного дискурсу. Також детально висвітлено основні характеристики професіограми сучасного оратора, що, на думку автора, є важливим елементом у підготовці риторичної особистості, запропоновано прийоми навчання етично дієвому дискурсу на уроках мови в основній школі. В статье выясняется смысл и значение этического общения в процессе становления идеальной риторической личности. В исследовании определены сущностные элементы риторического дискурса (предмет, продукт, средства реализации), подано содержательные характеристики этичности публичной речи, проанализированы аспекты выработки этически действенного риторического дискурса. Также подробно освещены основные характеристики профессиограммы современного оратора, что, по мнению автора, является важным элементом в подготовке риторической личности, предложено приемы обучения этически действенного дискурса на уроках языка в основной школе. Nowadays Rhetoric studies the relationships between the thought and the word and offers the effective methods of transformation the information into persuasive discourse. Today’s society needs to know the universal rules of creating ethical effectiveness in rhetorical discourse for harmonization in the process of communication. The main aim of the article is to look through the theoretical basis of rhetorical discourse generation and emphasize the conditions in which the discourse is considered to be ethical and effective. Rhetorical discourse includes some key concepts of main rhetorical qualities. Ethical effectiveness consists of the ethical correctness and ethical negotiability. The ethical correctness deals with moral standards of a good speaker. The ethical negotiability is based on the analysis of the audience and determines the speaker position and the behavior in further speech. Analysis carried out on the rhetoric researches proves that ethical effectiveness can be reached in such cases: 1) speaker’s great attention to moral standards and spiritual values; 2) discourse arrangement due to audience expectations on the basis of audience structure; 3) speaker’s orientation to the ideal of rhetoric culture; 4) harmonization in the process of communication with the help of creation and approval the primacy of ethicality in speech conversation. Such conversation is possible in the condition of relevant using of speech ethical forms, ethical formulas, euphemisms, ethical argument, direct and indirect forms of influence on the audience. However it could be noted that Rhetoric offers the efficient strategies and tactics of speech behavior which can develop the skills of everyone to carry responsibility for ethics in public speaking.